Shifts in community size structure drive temperature invariance of secondary production in a stream‐warming experiment. Issue 7 (12th June 2017) - Nelson, Daniel; Benstead, Jonathan P.; Huryn, Alexander D.; Cross, Wyatt F.; Hood, James M.; Johnson, Philip W.; Junker, James R.; Gíslason, Gísli M.; Ólafsson, Jón S.
Abstract: A central question at the interface of food‐web and climate change research is how secondary production, or the formation of heterotroph biomass over time, will respond to rising temperatures. The metabolic theory of ecology (MTE) hypothesizes the temperature‐invariance of secondary production, driven by matched and opposed forces that reduce biomass of heterotrophs while increasing their biomass turnover rate (production : biomass, or P : B ) with warming. To test this prediction at the whole community level, we used a geothermal heat exchanger to experimentally warm a stream in southwest Iceland by 3.8°C for two years. We quantified invertebrate community biomass, production, and P  :  B in the experimental stream and a reference stream for one year prior to warming and two years during warming. As predicted, warming had a neutral effect on community production, but this result was not driven by opposing effects on community biomass and P : B . Instead, warming had a positive effect on both the biomass and production of larger‐bodied, slower‐growing taxa (e.g., larval black flies, dipteran predators, snails) and a negative effect on small‐bodied taxa with relatively high growth rates (e.g., ostracods, larval chironomids). We attribute these divergent responses to differences in thermal preference between small‐ vs. large‐bodied taxa. Although metabolic demand vs. resource supply must ultimately constrain community production, our results highlight the potential for idiosyncratic community responses to warming, driven by variation in thermal preference and body size within regional species pools.